Analisis Minat Konsumen Terhadap Keputusan Pembelian Produk Pertanian “Tanaman Hias” Melalui Aplikasi Shopee - Lestari, Anik; Tria Rosana; Wardani, Irma (Agrisaintifika: Jurnal Ilmu-ilmu Pertanian, 2023)
The purpose of this research is to find out and analyze the influence of customer reviews, customer ratings and the existence of promos or discounts on purchasing decisions for ornamental plant agricultural products through the Shopee application. The research method used is a quantitative method. The scope of this research is the people of Boyolali Regency who use the Shopee application and purchase Ornamental Plant Agricultural Products. The sampling method is using the quota sampling method, with a sample of 50 respondents, with the following characteristics: Respondents are users of the shopee application, Respondents are buyers or customers who buy ornamental plant agricultural products, Respondents are domiciled in Boyolali Regency. For data collection techniques carried out in this study, namely by distributing questionnaires or questionnaires that were distributed using the Google form and data were processed using the SPSS application version 21. The results of this study are that the Customer Review Variable has a negative influence (-2.010) and is not significant on the purchasing decision of ornamental plant agricultural products through the shopee application in Boyolali Regency, the Customer Rating Variable has a positive direction (2.587) and is significant on purchasing decisions ornamental plant agricultural products through the shopee application in Boyolali Regency, the Variable of Promos or Discounts has a positive direction (3,787) and is significant on purchasing decisions for ornamental plant agricultural products through the shopee application in Boyolali Regency, Customer Review Variables, Customer Rating variables and the existence of variables Promos and discounts have an effect simultaneously (simultaneously) on purchasing decisions for ornamental plant agricultural products through the shopee application in Boyolali Regency.